2019
DOI: 10.9734/arrb/2019/v31i330050
|View full text |Cite
|
Sign up to set email alerts
|

Path Analysis and Genetic Parameters for Grain Yield in Bread Wheat (Triticum aestivum L.)

Abstract: The experiment was conducted with 2 replications and 54 genotypes of wheat consisting 10 lines, 4 testers and their 40 crosses made in line X tester mating fashion in randomized block design during growing seasons 2014-2015. Spike length recorded the highest value of broad sense heritability while Canopy temperature index reported the highest value of genetic advance as a percent of mean and also reported highest phenotypic and genotypic coefficient of variation. Genotypic path analysis revealed that test weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 3 publications
4
22
2
Order By: Relevance
“…The wheat cultivar DPW-621-50 was used to generate a mutant population. Seeds of DPW-621-50 were soaked in 0.7% (v/v) EMS solution (Sigma-Aldrich®) and kept at 75 rpm on a shaker overnight at room temperature (Dong et al, 2009 [4] ; Uauy et al, 2009) [4,13] . After EMS treatment, the seeds were thoroughly washed under running tap water for 6 h and then sown in the field at Norman E. Borlaug Crop Research Centre G.B.P.U.A.T, Pantnagar.…”
Section: Methodsmentioning
confidence: 99%
“…The wheat cultivar DPW-621-50 was used to generate a mutant population. Seeds of DPW-621-50 were soaked in 0.7% (v/v) EMS solution (Sigma-Aldrich®) and kept at 75 rpm on a shaker overnight at room temperature (Dong et al, 2009 [4] ; Uauy et al, 2009) [4,13] . After EMS treatment, the seeds were thoroughly washed under running tap water for 6 h and then sown in the field at Norman E. Borlaug Crop Research Centre G.B.P.U.A.T, Pantnagar.…”
Section: Methodsmentioning
confidence: 99%
“…Residual effects with 0.042 indicated that the studied eight characters account for about 95.68 % of the variability in the grain yield. In previous studies, major portion of total variability in grain yield was owing to characters such as spikes number, grain number and weight Mohamed, 2018 andRajput, 2019); grain-filling period and plant height (Mecha et al, 2017;Sabit et al, 2017 andBaye et al, 2020). Moreover, negative direct effect of days to maturity on grain yield was also reported (Dabi et al, 2016;Mecha et al, 2017;Sabit et al, 2017;Rajput, 2019;Baye et al, 2020 andKhanala et al, 2020).…”
Section: F3 Generationmentioning
confidence: 99%
“…Line by tester technique is an effective tool and has been widely used to assess different parental populations for combining ability, gene action, and to select promising genotypes for developing new wheat cultivars (Tiwari et al, 2017;Rajput, 2019). Combining ability can be divided into general combining ability (GCA) which is due to the additive type of gene action while specific combining ability (SCA) indicates the dominant gene action (Sprague and Tatum, 1942;Younas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%